Rethinking civil-military relations in Turkey: How has the security landscape changed under AKP rule? - Sinem Adar; Nebahat Tanrıverdi Yaşar (Stiftung Wissenschaft und Politik (SWP), 2023)
Speaking at the inauguration ceremony in June after being sworn in for the third time as the president of Turkey, Recep Tayyip Erdoægan promised the nation that his policies in the coming five years would "crown the second century of the republic with the Century of Türkiye". Turkey has undergone a massive transformation in the last two decades since the Justice and Development Party (AKP) rose to power in 2002. Undoubtedly, the reconfiguration of civil-military relations has been one of the most critical markers of such change. The Turkish Armed Forces (TAF) has, under AKP rule, become an executor of foreign policy in an empowered security ecosystem consisting of the Ministry of Interior (MoI), the National Intelligence Organization (MçIT), and the defence industry. These shifts in the security environment as such have been shaped by the dynamics of regime change in Turkey and post-Cold War security imperatives.
Keywords: 320; Turkey; Recep Tayyip Erdoægan; NATO; Justice and Development Party (AKP); Turkish Armed Forces (TAF); Ministry of Interior (MoI); National Intelligence Organization (MçIT); defence industry; Turkish National Police (TNP); Syria; Iraq; Libya; Somalia; Qatar